COLLOCATION AS A MINIMAL UNIT OF VOCABULARY ACQUISITION BUILDING IN ENGLISH LEARNING PROCESS - Zhelobytska, T. V. (НДУ імені Миколи Гоголя, 2020)
This paper presents an academic research primarily focuses on defining collocation as a minimal unit in vocabulary acquisition building, on its importance for English Learners during English Learning Process and finally on its main role in practical usage of the English language. The main objectives were realized through various materials exploration of general English vocabulary acquisition building in Canadian English (CE), American English (AE), and British English (BE). The research area was original Canadian, American, and British informational sources with special emphasis on different scholars’ ideas as for English spoken language and vocabulary load in written texts. The research highlighted the significance of collocations through their necessary and completely right usage in English Teaching and Learning Processes. The investigation made it possible to specify the definition of ’collocation’ and provide background information about collocations by gathering and analyzing Contemporary Linguistics scientists’ works and expressed their opinions. General scientific methods include deduction and induction, observation and generalization. Major linguistic methods employed in this paper are the structural (a definitive and distributional analysis) and contrastive (based on three variants of English) ones. The methodology used for this academic research is simple being profound and scientifically approved. The notion of ’collocation’ refers to the frequent co-occurrence and mutual expectation of some words which appear more often than by chance. In this sense, collocation can be called ’a restricted combination’, which exists between a free combination and an idiom and has semantic transparency. The study of collocations was scanned through modern international researchers of CE / AE / BE. On having specified the definition of collocation and then shown the importance of collocations usage, we could finally provide some recommendations for the teaching and learning processes of collocations in order to improve and refresh modern English studies for students of linguistics / philology departments. These recommendations are as follows: teach / learn English via modern CE / AE / BE sources; emphasize on collocations structure and meaning during English Teaching and Learning vocabulary; pay a special attention to difference in similar collocations among various variants of English (for instance, as presented for CE / AE / BE in this paper);give preference to teaching / learning materials in native English; encourage students to read and listen to genuine CE / AE / BE written by native speakers; make use of online dictionaries, free corpora, and the Internet rich materials on a regular basis. Nowadays, there are many excellent dictionaries of CE / AE / BE collocations which are free and easy to be accessible. The prospects for further study may cover building of a digital dictionary of most frequent collocations in Canadian English, American English, and British English.
Keywords: collocation; minimal unit; vocabulary acquisition building